P254 Predicting who needs a humidifier with CPAP. (14th November 2013) - Thirugnanasothy, L; Littlemore, J; Oliver, J; Close, P; West, SD
Abstract : Introduction: Some patients using continuous positive airway pressure (CPAP) for the treatment of Obstructive Sleep Apnoea (OSA) require the addition of a heated humidifier to their CPAP machine. This is used to combat symptoms of dry nose and mouth and blocked nose which may limit CPAP adherence. We sought to establish whether there are any patient predictors for whether a humidifier will subsequently be needed. This might allow provision of more economical integrated CPAP/humidifiers. Methods: All patients commencing CPAP over a one year period completed a questionnaire with a member of the Sleep team at the time of CPAP set-up. The questionnaire asked about symptoms prior to CPAP including blocked, dry or runny nose and dry mouth on waking. Details of sleep study parameters such as ODI and AHI were obtained from hospital notes, along with anthropometric measures of body mass index (BMI) and neck size. The questionnaire also enquired about previous medical history (including ENT surgery), medications, smoking history and bedroom environment. Patients were given humidifiers according to usual practice as required after CPAP commencement, according to symptoms. The CPAP database was reviewed at the time of analysis to determine which patients had received humidifiers. Results: Questionnaires were completed by 185 people commencing CPAP from January 2012. The mean (SD) age of this group was 53 years (11.7), BMI 36.6 kg/m 2 (7.1), neck size 43.9cm (4.4), ODI 29.3 (23). The proportions of different severities of OSA were 19% mild, 34% moderate and 47% severe. The frequencies of symptoms prior to CPAP were 87% dry mouth, 54% blocked nose, 40% dry nose and 22% runny nose. In this cohort, 43% of people were given a humidifier. There were no statistically significant correlations of any of the variables with humidifier outcome. Chi squared analysis showed no significant difference in the proportion of those people with humidifier versus those without for any of the questionnaire categories. Conclusion: It does not appear to be possible to prospectively predict which patients will require a humidifier with their CPAP. Current practice of symptom-led humidification appears valid.